Letter (copy) : Bombardment of open towns in Spain - McDonald, Florence
012a-0095-001 Secretary's. FEM/KMS/547 23th April, 1938. Mr. P. Thurtle, Private Secretary to the Rt.Hon. C.R. Attlee, M.P. House of Commons, S.W.1. Dear Mr. Thurtle, BOMBARDMENT OF OPEN TOWNS IN SPAIN. With reference to my telephone conversation with you this afternoon, I am enclosing a copy of two relevant paragraphs from the letter of General Julius Deutsch, Ambassada d'Espagne, Paris, dated 27th April, 1938, with regard to the bombardment of open towns in Spain. Yours sincerely, Private Secretary. Enc. Copy. 292/946/12a/95